Impact of Twin wheel here for Weeding Drudgery Reduction of Farm Women - Mishra, Reeta; Mishra, Y. D.; Singh, P. P.; Raghubanshi, B.P.S. (Indian Journal of Extension Education, 2018)
The present investigation was carried out to evaluate the weeding efficiency of tools and performance evaluation of  weeding activity performed by farm women using newly introduced and traditional tools. The study included a sample of  20 farm women of Morena district. SWOTanalysis indicates that use of improved tools by farm women for weeding could  be a useful implementation for reducing the drudgery of farm women with increased output. The interest of farm women  was stimulated by explaining to them how it could contribute towards their drudgery reduction. Atraining programme for  this group of women beneficiaries for their empowerment was organized to impart knowledge and skill of improved farm  tools. The wheel hoe is found highly acceptable tool as compared to traditional khurpi. Twin wheel hoe was perceived  more suitable for weeding by farm women.
Keywords: Drudgery; SWOT; twin wheel here; weeding